Analysis of Productivity Loss In Ironing, Formwork, and Casting Work at Summarecon Mall Bandung Project - Johansen Ridawaputra, Samuel; Fachreza, Muhammad; Abdurahman Faizi , Darda (Jurnal Indonesia Sosial Teknologi, 2024)
In a developing country such as Indonesia, infrastructure development is one of aspects that contribute to advancement for the country. However, construction industry in Indonesia has a problem regarding to low construction productivity. Lean construction regarded as the new method to improve construction performance and labor productivity. Using two principles of lean construction, benchmarking and labor production variability reduction will be analyzed to show how impact it caused to labor performance. Benchmarking will be used to analyze for Summarecon Mall Bandung Project with parameters of Disruption Index (DI), Perfomance Ratio (PR) and Project Manajemen Index (PMI). The project has DI<0,1 score that means abnormality days that happened was low, varied PR score in all construction operation, and low PMI score that represent good construction management system. In conclusion based on all parameters, Mall Summarecon Bandung Project is relatively good project and can be used as a benchmark for similar construction project.